ANALISA PENGARUH PERLAKUAN PANAS SEBELUM DAN SESUDAH PENEMPERAN TERHADAP NILAI KEKERASAN PADA BAJA PERKAKAS HSS - Asmara, Anjar (MEKTEK, 2005)
The purpose of this research is to understand the effect of heat treatment before and after tempering on hardness with temperature variation of HSS steel. Heat treatment with temperature 500- 850 oC on specimens were tested and quenched on the water. Another specimen was tempered with 100, 250, 400, 500, 600 and 700 oC temperatures with air quenching. Hardness testing of these specimens has been done with Vickers and Rockwell method. Results show that heat treatment process with water quenching increases hardness and specimens tend to decrease their hardness with increasing temperature